Organization of individual afferent axons in layer IV of striate cortex in a primate - Florence, SL (J Neurosci, 1987)
Evidence from a number of anatomical and physiological studies shows that information is transmitted from the retina to visual cortex via physiologically and anatomically distinct populations of neurons in the lateral geniculate nucleus (LGN). In order to gain a better understanding of the functional roles of these parallel channels from the LGN to cortex in primates, individual afferent axons to layer IV of striate cortex of galagos were filled with HRP by bulk injection into the white matter underlying striate cortex. A total of 55 axons and their terminal arbors, from zones representing both the central and peripheral visual fields, were completely reconstructed through serial sections. Based upon the sublaminar distribution and the morphology of these axons, they have been categorized into 2 groups, designated type I and II axons. Evidence from both past work and the present study suggests that type I axons represent the projections from physiologically defined Y-like cells in the magnocellular layers of the LGN, while type II axons represent the projections from X-like cells in the parvocellular LGN layers. Our results show that type I (presumed Y- like) arbors occupy relatively more cortical space within their main terminal sublayer (IV alpha) than is the case for the type II (presumed X-like) arbors which ramify primarily in layer IV beta. In addition, type I arbors have larger parent axons, fewer boutons along a restricted length of axon, and a greater tendency to branch in layer VI than type II arbors. Finally, both axon types are larger in the area of cortex representing central vision than in the area representing peripheral vision. These morphological characteristics suggest that the physiological differences between magnocellular and parvocellular geniculate cells may be amplified in cortex by differences in the organization of their terminal arbors. Further, within each afferent population, the terminal organization of axons reflects their visuotopic relationships in striate cortex. Comparison of these findings with data from cats and monkeys supports the idea that the relationship between the size of the terminal arbors of LGN X-like or parvocellular cells and the size of the cortical spatial subunit varies with differences in visual acuity across species; for LGN Y-like (or magnocellular) cells this relationship remains constant.